Impact of New-Onset Conduction Disturbances following Transcatheter Aortic Valve Replacement on Outcomes: A Single-Center Study - Claudia See; Yanting Wang; Haocheng Huang; Helen Parise; Yiping Yang; Daniela Tirziu; Dominic P. Francese; Nikolaos Papoutsidakis; Eric Bader; Ryan K. Kaple; Michael Cleman; Alexandra J. Lansky; et al. (Journal of Interventional Cardiology)
Background. Transcatheter aortic valve replacement (TAVR) is known to increase the incidence of conduction disturbances compared to surgical aortic valve replacement; however, there are limited data on the impact and duration of these conduction disturbances on longer term outcomes. Objective. To determine the differential impact of persistent versus nonpersistent new-onset conduction disturbances on TAVR-related complications and outcomes. Methods. This is a single-center retrospective analysis of 927 consecutive patients with aortic stenosis who underwent TAVR at Yale New Haven Hospital from July 2012 to August 2019. Patients with new-onset conduction disturbances within 7 days following TAVR were selected for this study. Persistent and nonpersistent disturbances were, respectively, defined as persisting or not persisting on all patient ECGs for up to 1.5 years after TAVR or until death. Results. Within 7 days after TAVR, conduction disturbances occurred in 42.3% (392/927) of the patients. Conduction disturbances persisted in 150 (38%) patients and did not persist in 187 (48%) patients, and 55 (14%) patients were excluded for having mixed (both persistent and nonpersistent) disturbances. Compared with nonpersistent disturbances, patients with persistent disturbances were more likely to receive a PPM within 7 days after the TAVR procedure (46.0% versus 4.3%, p<0.001) and had a greater unadjusted 1-year cardiac-related and all-cause mortality risk (HR 2.54, p=0.044 and HR 1.90, p=0.046, respectively). Conclusion. Persistent conduction disturbances were associated with a greater cardiac and all-cause mortality rate at one year following TAVR. Future research should investigate periprocedural factors to reduce persistent conduction disturbances and outcomes beyond one year follow-up.